Effect of Temperature and Pressure in Producing Thick Cassava Chips Using Vacuum Frying - Sandi Asmara (Research and Social Study Institute, 2022)
Lampung province is one of Indonesia's cassava production centers. Lampung Province is currently Indonesia's largest cassava producing area, capable of producing 60 percent of the country's tapioca needs. Cassava chips are not a new product for Indonesians. Processing cassava into thick cassava chips using vacuum frying technology is a promising technology that can increase the economic value of cassava tubers while also meeting consumer demand for innovation in the shape and size of cassava chips. The problems investigated in this study include determining the optimal temperature required to produce thick cassava chips of the highest quality and the optimal pressure required to produce thick cassava chips of the highest quality. The aims of this study was to determine the optimum temperature and pressure required to produce thick cassava chips with the best quality at temperatures of 80 C, 85 C, and 90 C and pressures of -65 cmHg, -68 cmHg, and -72 cmHg. Data analysis in Microsoft Excel software using Anova analysis to determine the effect of temperature and pressure on frying time, moisture content, weight loss, and organoleptic test. The effect of temperature and pressure on the frying using vacuum frying in the manufacture of thick cassava chips was studied. Temperature and pressure affect the water content, length of frying, and organoleptic test of aroma, color, taste, and crispness. The best quality of thick cassava chips has the lowest moisture content of 3.01% and the shortest frying time of 38 minutes, as well as the favorite score of the hedonic aroma test 3.87, taste 4.37, color 4.17, and crispness 4.73 on a scale of 1-5 contained in the treatment with optimal temperature and pressure, temperature 90 C and pressure -72 cmHg.